SK3 Trafficking in Hippocampal Cells: The Role of Different Molecular Domains. Issue 6 (17th November 2006) - Decimo, Ilaria; Roncarati, Renza; Grasso, Silvia; Clemens, Marcel; Chiamulera, Christian; Fumagalli, Guido
Abstract : The regulative steps that control trafficking of ion channels are fundamental determinants of their qualitative and quantitative expression on the cell membrane. In this work the trafficking of the small conductance calcium-activated potassium channel, SK3 was studied in neurons in order to identify relevant molecular domains involved in this process. Hippocampal cell cultures were transfected with fusion proteins of green fluorescent protein (GFP) and different SK3 subunit truncations. The differential distribution of the mutants was analyzed by confocal microscopy and compared to the localization of the control fusion protein with full length SK3. The transport of chimeric proteins was quantified from fluorescence images by developing a morphometric analytical method. We found that the full length SK3 was distributed in cell body, axon and dendrites, whereas the deleted forms GFPΔ578–736 (deletion of the entire C-terminal domain), GFPΔCaMBD (deletion of the calmodulin-binding site) and GFPΔN (deletion of the N-terminal domain) were not transported into cell processes but accumulated in the cell body. The GFPΔ640–736 (deletion of the distal C-terminal domain) showed a distribution similar to control. The quantification and statistical analysis confirmed the differences in distribution across the three groups. In conclusion, the current work provides evidence for a fundamental role of the N-terminal domain and the calmodulin binding domain in SK3 trafficking in neurons.